Increasing The Students’ Critical Thinking Through Inquiry Learning on System of Senses Subject At Class XI MIA 6 SMA N 4 Surakarta Class Year of 2014/2015 - Wahyu Setiya Roning Perdani; Slamet Santosa; Murni Ramli; Yulianto Edi Martono (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
The aim of this research is to increase the students’ critical thinking through inquiry learning. This research was a classroom action research with 3 cycles conducted from March until April 2015. Each cycle consisted of 4 phases, i.e. planning, acting, observing, and reflecting. The participants of the research are 34 students of grade XI MIA 6 SMAN 4 Surakarta. Data was obtained from questionnaire, multiple choices test, and interview. The main data of the students’ critical thinking includes several aspects as follows: interpretation, analysis, evaluation, inference, explanation, and self-regulation. Data was analyzed descriptively, and validated using a triangulation method. The research procedure used was the spiral method by Kemmis and Mc.Taggart. The result of the research shows that inquiry learning increased the students’ critical thinking. The student’s critical thinking from the pre cycle is 35,04 %, the first cycle is 42,40 %, the second cycle is 51,71 %, the third cycle is 63,97 %.Keywords: Inquiry Learning, Critical Thinking, System of  Senses